TEACHERS' EFFORTS TO COOPERATE WITH PARENTS IN GUARANTEEING THE GROWTH AND DEVELOPMENT OF STUDENTS' CREATIVITY - Haudi (Adisam Publisher, 2024)
This comprehensive literature review explores the multifaceted dimensions of optimizing teachers' efforts to collaborate with parents in overseeing the growth and development of students' creativity. The role of the teacher is very important in the learning process because the teacher is an educator, teacher, guide, director, trainer and assessor or evaluator of students. As a teacher, you must be able to create an atmosphere of an active and creative learning process, so that learning is not boring for students and teachers must be able to increase students' learning creativity. Teachers have the power to instill values and character in children. In instilling values, there is the value of students' creativity which needs to be monitored for their growth and development. Apart from receiving attention from teachers, the role of the family, especially parents, is very important in meeting the physical needs of students which supports the development and formation of children's creativity. There are five ways that educational institutions can use to establish relationships with the community, namely through student curricular activities, through teacher activities, through extracurricular activities, community visits to educational institutions and the mass media.